Teaching Biology for Sustainability: Insight from Scopus AI - Husamah, H.; Rahardjanto, Abdulkadir; Permana, Tutut Indria (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
In the face of escalating environmental crises, climate change, and global sustainability challenges, biology education holds a critical role in shaping ecological literacy and responsible citizenship. This study conducted an AI-assisted scoping review using Scopus AI to synthesize key insights, methods, and emerging themes in teaching biology for sustainability between 2020–2025. From N records retrieved, M studies met inclusion criteria for qualitative synthesis based on abstracts and Scopus AI summaries. Using both natural language and keyword-based searches, the study systematically identified peer-reviewed journal articles that explore sustainability integration in biology and life science education. A PRISMA-guided process was applied to ensure transparent identification, screening, and inclusion. The retrieved data were analyzed qualitatively to map pedagogical innovations, thematic clusters, and conceptual linkages among core sustainability elements. Findings indicate that approximately X of M studies emphasize project-based or problem-based learning, while Y address biomimicry or systems thinking approaches. Effective sustainability-oriented biology education is grounded in the integration of Education for Sustainable Development (ESD) and systems thinking, supported by student-centered pedagogies such as problem-based, project-based, and experiential learning. Additionally, biomimicry and digital learning technologies—including online multimedia tools and Electronic/Mobile/Ubiquitous (E/M/U) learning—emerge as transformative approaches that enhance student engagement, critical thinking, and ecological responsibility. Equity and feasibility issues remain critical, particularly concerning bandwidth limitations, access to devices, and inclusivity for students with disabilities. Therefore, low-cost, accessibility-aware strategies such as biomimicry mini-projects and E/M/U-enabled ecological audits are recommended. Despite these advances, challenges remain concerning educator readiness, risk of indoctrination, and institutional constraints. The concept map generated through Scopus AI highlights three interconnected clusters—Ecological Awareness, Student-centered Pedagogies, and Sustainability Education—reflecting a shift from content transmission to transformative learning. Overall, this review concludes that biology education must evolve beyond content mastery to integrate ethical, technological, and transdisciplinary dimensions—empowering learners not only to understand life but to sustain it—aligned with SDG 4 (Quality Education), SDG 13 (Climate Action), and SDG 15 (Life on Land).